Development of an Augmented Reality-Integrated Student Worksheet (LKPD) to Enhance Mathematics Learning Outcomes - Sri Murni Hidayani; Arif Muchyidin; Arif Abdul Haqq (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aims to develop and assess the quality of an Augmented Reality-Integrated Student Worksheet (LKPD) to enhance seventh-grade students' mathematics learning outcomes in spatial geometry. The research follows the Plomp development model, consisting of four phases: preliminary investigation, design, realization, and test-evaluation-revision. The LKPD was validated by three experts, including two mathematics education specialists and one instructional design expert. Practicality tests were conducted with one mathematics teacher and 31 students from SMP Negeri 16 Cirebon. The validation results indicate that the LKPD is highly valid, with a content validity score of 87.56% and a design validity score of 87.22%. Practicality tests showed positive responses from teachers (80%) and students (72.30% in small groups and 77.64% in field trials). Based on pre-test and post-test results, effectiveness testing yielded an N-Gain score of 0.58, categorized as moderate effectiveness. These findings suggest that the Augmented Reality-Integrated LKPD is a feasible and effective learning tool for mathematics education. However, limitations include compatibility issues with Android versions above 10 and dependency on coloured markers for AR recognition. Future research should focus on improving AR functionality for broader accessibility.